Electronic identification systems reduce the number of wrong components transfused - Murphy, MF; Addison, J; Poles, D; Dhiman, P; Bolton-Maggs, P (Wiley, 2019)
Background: Errors in hospital transfusion may cause wrong (blood) components to be transfused. This study assessed the value of electronic identification systems (EISs) in reducing wrong component transfusions (WCTs).